Estimation of externalities due to impact of solid waste dumping on crop farming and valuation of crop lands in Tamil Nadu - R Sunandhini; C Sekar (Agricultural Economics Research Review, 2023)
Growing urbanization generates large quantities of solid waste. In the absence of efficient management, this waste pollutes surface and groundwater sources and soils. We assess the effects of such externalities on agriculture in terms of crop damage. The distance of the farmland from the dump yard and averting expenditure are found negatively significant in finding the intensity of pollution and losses of yield in monetary terms. Water quality, farm size, distance between the farm land and dump yard are found to be positively significant in deciding the value of crop land, and nearness to highways negatively significant.